2020
DOI: 10.1002/ccd.29198
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on interventional cardiology training in the United States

Abstract: Objectives We sought to determine the effect of COVID‐19 related reduction in elective cardiac procedures and acute coronary syndrome presentations on interventional cardiology (IC) training. Background The COVID‐19 pandemic has significantly disrupted healthcare in the United States, including cardiovascular services. The impact of COVID‐19 on IC fellow training in the United States has not been assessed. Methods The Society for Cardiovascular Angiography and Interventions (SCAI) surveyed IC fellows training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 11 publications
1
33
0
1
Order By: Relevance
“…Specific to COVID-19, physicians in China [ 56 ], France [ 196 ], India [ 40 , 50 , 58 ], Pakistan [ 157 , 192 ], South Korea [ 184 ], Tunisia [ 192 ], Turkey [ 44 ], and USA [ 99 , 103 , 105 , 203 ] expressed desire for their organizations to provide access to psychological support through counselling programs or support hotlines ( n = 13). Communication and appreciation from hospital administrators ( n = 4) was indicated as an important gesture to help foster feelings of gratitude for physicians in China [ 108 , 115 ], Colombia [ 201 ], and the USA [ 52 ] [ 52 , 58 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific to COVID-19, physicians in China [ 56 ], France [ 196 ], India [ 40 , 50 , 58 ], Pakistan [ 157 , 192 ], South Korea [ 184 ], Tunisia [ 192 ], Turkey [ 44 ], and USA [ 99 , 103 , 105 , 203 ] expressed desire for their organizations to provide access to psychological support through counselling programs or support hotlines ( n = 13). Communication and appreciation from hospital administrators ( n = 4) was indicated as an important gesture to help foster feelings of gratitude for physicians in China [ 108 , 115 ], Colombia [ 201 ], and the USA [ 52 ] [ 52 , 58 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety (n = 103), depression (n = 73), stress (n = 68), fear (n = 61), burnout (n = 25), mental distress/health (n = 21), and post-traumatic stress disorder (PTSD) (n = 14) (Additional File 3). Most COVID-19 studies reported on physicians from USA (n = 23) [41,52,66,70,77,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107], China (n = 22) [15, 49, 54-56, 65, 68, 73, 86, 89, 102, 108-118] followed by India (n = 21) [40,50,58,63,67,71,102,[119][120][121][122][123][124][125][126][127][128][129][130][131][132] [41,52,…”
Section: Experiences With Physician Psychological Symptoms During Infectious Disease Outbreaksmentioning
confidence: 99%
“…4,5 The predictable downstream financial effects of these constraints have been discussed, 6 and there is much concern about the impact on trainees. [7][8][9] To our knowledge, our survey is the first to document specific changes in procedural and clinical exposure for CCEP trainees due to the pandemic. July 2020 were ready for independent practice.…”
Section: Methodsmentioning
confidence: 99%
“…The virus spread and resulted in a marked upsurge in hospitalizations and deaths worldwide, stretching health care services to a breaking point, even in countries with very robust health care infrastructures [7]. There was thus a redistribution of health care resources to cater to the burgeoning number of COVID 19 infections to the detriment of other services [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%